Pengaruh Kualitas Layanan Aplikasi Maxim Terhadap Customer Loyalty Dengan Kepuasan Pelanggan Sebagai Variabel Intervening - Kinarya Agung Nograha; Ezizwita (GLOBAL SCIENTS PUBLISHER, 2025)
The purpose of this study is to determine and analyze the effect of Maxim App Service Quality on Customer Loyalty, with Customer Satisfaction as an intervening variable. The population of this study was Maxim App consumers, whose exact number is unknown. The sample in this study was 130 Maxim App consumers. This study was conducted using a purposive sampling method, which determines the sample based on suitability to certain characteristics and criteria. The data for this study were obtained from questionnaires distributed directly to respondents. The analysis method used was quantitative, using Smart Pls-4. The results show that Service Quality has a positive and significant effect on Customer Satisfaction; Customer Loyalty has a positive and significant effect on Customer Satisfaction; and Service Quality has a negative but insignificant effect on Customer Loyalty on Purchasing Decisions.